Nanotechnology and processes the nano-photovoltaic panels - Ferreira, M. A. M.; Filipe, J. A.; Chavaglia, J. N. (Advanced Materials Research, 2014)
Nanotechnology can be a powerful weapon in creating competitive advantages in the energy market, through the use of the photovoltaic Nano-panels, which may reduce production costs and simultaneously permit to achieve the socio-environmental requirements. Moreover, today the adoption of nanotechnology in energy production can make this kind of energy very interesting along the years. Nanotechnology may, in fact, be responsible for unimaginable gains, both economically and for preserving the planet. The use of nanotechnology in the industry production processes is evidenced in this article. The example of the electric energy produced by photovoltaic panels is the vehicle to do so. The competitive advantage associated to the use of nanotechnology to solar energy production for companies in this market segment is highlighted. Finally, in addition to the already existent Nano-panels, another opportunity to revolutionize the market, already in sight, is presented: the Nanogenerators that can convert the mechanical energy of body motion in electricity.